FAKTOR PENYEBAN KECEMASAN KELUARGA PASIEN RAWAT INAP BANGSAL KEBIDANAN dan BANSAL PENYAKIT DALAM dI RUMAH SAKIT UMUM DAERAH (RSUD) PARIAMAN - Prionata, Andri - (Bimbingan dan Konseling, 2014)
The problem that would be researched by the researcher based on the phenomenon in the field, patient family has anxiety in taking care of hospitalization patient. Then, the researcher pulled up the problem about the cause of factors of anxiety from patient family in take care the patient at District Public Hospital of Pariaman. The purposes of this research was to describe about intrinsic factors and extrinsic factors of causes the anxiety from hospitalization of patient family in obstetric shed and internist shed at District Public Hospital of Pariaman. This research was descriptive quantitative research. The populations of this research were the family of hospitalization patient in obstetric shed and internist shed at District Public Hospital of Pariaman and there were 29 persons. The researcher used total sampling as the technique to take the sample. It meant, there were 29 persons as the sample. The instrument that was used in this research was questionnaire, while for the data analysis, the researcher used percentage technique. The results of this study showed that: 1) intrinsic factors of causes the anxiety from hospitalization of patient family in obstetric shed and internist shed is in many category, that is 72,41%. 2) Extrinsic factor of causes the anxiety from hospitalization of patient family in obstetric shed and internist shed is in many category, that is 62,06%. These results recommended to the hospital in order to increase the quality of service, so the curing of patient will run well and also the patient family feel comfort and avoid from any anxiety.